2021
DOI: 10.1017/s0025315421000862
|View full text |Cite
|
Sign up to set email alerts
|

Lacydonia shohoensis (Annelida, Lacydoniidae) sp. nov. – a new lacydonid species from deep-sea sunken wood discovered at the Nishi-Shichito Ridge, North-western Pacific Ocean

Abstract: Lacydonia Marion & Bobretsky, 1875 is the sole genus in the family Lacydoniidae Bergström, 1914. We herein describe the new species of Lacydonia shohoensis sp. nov. from 2042-m deep bottoms at Shoho Seamount of the Nishi-Shichito Ridge, the Northwest Pacific Ocean. It is most similar to L. anapaulae Rizzo et al., 2016 in having a depression on the median anterior region and lacking lateral lobes on the posterior margin of prostomium whereas it is distinguished by possessing pygidium dorsally pigmented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…As a result, the May 2021 WDPA and WD-OECM showed that at least 22.5 million km 2 (16.64%) of land and inland water ecosystems, as well as 28.1 million km 2 (7.74%) of coastal waters and the ocean, are within protected areas and OECMs (UNEP-WCMC and IUCN, 2021). However, the understanding of the biodiversity in protected and conserved areas remains relatively poor, especially in offshore environments (Vad et al, 2017;Ferrari et al, 2018;Hookabe et al, 2021;Koeda et al, 2021;Hookabe et al, 2022;Jimi et al, 2022;Komai et al, 2022). In fact, all newly discovered habitats of the Yokozuna Slickhead, with the exception of the Genroku Seamount, are in the MPAs established in 2020 in Japanese waters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the May 2021 WDPA and WD-OECM showed that at least 22.5 million km 2 (16.64%) of land and inland water ecosystems, as well as 28.1 million km 2 (7.74%) of coastal waters and the ocean, are within protected areas and OECMs (UNEP-WCMC and IUCN, 2021). However, the understanding of the biodiversity in protected and conserved areas remains relatively poor, especially in offshore environments (Vad et al, 2017;Ferrari et al, 2018;Hookabe et al, 2021;Koeda et al, 2021;Hookabe et al, 2022;Jimi et al, 2022;Komai et al, 2022). In fact, all newly discovered habitats of the Yokozuna Slickhead, with the exception of the Genroku Seamount, are in the MPAs established in 2020 in Japanese waters.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020 and 2021, two research cruises were conducted to develop biodiversity monitoring methods for the management of deep-sea marine protected areas (MPAs) and monitoring the deepsea MPAs in Japanese waters (Hookabe et al, 2021;Koeda et al, 2021;Hookabe et al, 2022;Jimi et al, 2022;Komai et al, 2022). To understand fish diversity including large predatory consumers, metabarcoding analyses of fish and baited camera observations were conducted on/around six seamounts on the Nishi-Shichito Ridge as well as the Central and Western Mariana ridges, which are designated as MPAs.…”
Section: Introductionmentioning
confidence: 99%